THE ANALYSIS OF ENGLISH USED BY BROADCASTERS OF MUSIC PROGRAMS IN BANJARMASIN - Athiya, Husnul (English Department of Faculty of Tarbiyah and Teachers Training, 2017)
This article investigated about language used phenomenon in broadcasting field. It focused on why the broadcasters tend to mix their language with English while speaking. The subjects are four broadcasters from two radio stations, DBS FM and RRI Pro 2. The object is reasons of doing code switching into English during the broadcast. The writer uses recording, interview, and documentary techniques. After collected, the data are analyzed with theories and explained descriptive-qualitatively. The result shows that the reasons of using English are because they have been accustomed to saying those words in English, their perception of English as sophisticated language, they want to make variation on their broadcast, imitating someone, make special characteristics, forgot the Indonesian words, adjusting with the program and the listeners, and lazy to translate the script into Indonesian